2002
DOI: 10.1021/bc015588t
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Two Tamoxifen Target Proteins by Photolabeling with 4-(2-Morpholinoethoxy)benzophenone

Abstract: Our quest to identify target proteins involved in the activity of tamoxifen led to the design of photoaffinity ligand analogues of tamoxifen able to cross-link such proteins. A new tritiated photoprobe, 4-(2-morpholinoethoxy)benzophenone (MBoPE), was synthesized and used to identify proteins involved in tamoxifen binding in rat liver. MBoPE, which has structural features in common with the potential antagonist of the intracellular histamine receptor (N,N-diethyl-2-[(4-phenylmethyl)phenoxy]ethanamine HCl: DPPE)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 41 publications
0
24
0
Order By: Relevance
“…19 hCE1 was not thought to be involved in the trafficking of tamoxifen through the body until it was found that only four proteins in rat liver bound a labeled form of tamoxifen, and one of these proteins was the rat homologue of hCE1. 20 Thus, it is possible that the binding of tamoxifen to hCE1 may limit the bioavailability of the drug, or may lead to drug-drug interactions and/or side-effects associated with tamoxifen use, including impact on cholesterol levels. 21 In addition to its role in xenobiotic metabolism, hCE1 has been shown to catalyze reactions involved in cholesterol homeostasis and fatty acid metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…19 hCE1 was not thought to be involved in the trafficking of tamoxifen through the body until it was found that only four proteins in rat liver bound a labeled form of tamoxifen, and one of these proteins was the rat homologue of hCE1. 20 Thus, it is possible that the binding of tamoxifen to hCE1 may limit the bioavailability of the drug, or may lead to drug-drug interactions and/or side-effects associated with tamoxifen use, including impact on cholesterol levels. 21 In addition to its role in xenobiotic metabolism, hCE1 has been shown to catalyze reactions involved in cholesterol homeostasis and fatty acid metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…In these tissues, a biomacromolecule was observed to bind tamoxifen and other estrogenic derivatives, including ICI 47699 (Murphy & Sutherland 1981a), and displays tissue-specific differences in cellular concentration . This substance was subsequently named the microsomal antiestrogen-binding site (AEBS); a hetero-oligomeric multiprotein complex found in most mammals in different tissue-dependent concentrations (Mésange et al 2002, Kedjouar et al 2004. For example, AEBS is w20-30 times more abundant in the liver when compared with tumor cell lines (Chailleux et al 1994).…”
Section: Biochemical History Of the Dual Agonist/ Antagonist Activitymentioning
confidence: 99%
“…For this reason, the liver have been chosen for the purification of the AEBS but the pharmacological profiles of the AEBS found in the liver and in tumor cell lines such as MCF-7 cells (a mam-mary adenocarcinoma cell line) have been reported to be different, suggesting a possible difference in the composition of the AEBS in the two systems (19). We have recently reported that the AEBS from rat liver was a hetero-oligomeric multiprotein complex that contained subunits that were not directly involved in the binding of tamoxifen such as the microsomal epoxide hydrolase (mEH) (20), the carboxyl-esterase (ES-10), and the liver fatty acid-binding protein (FABP) (21). Each of these proteins have been implicated in lipid metabolism: mEH is a bile acid transporter (22), and carboxylesterase has cholesterol esterification properties (23) but were related to the AEBS found in normal liver because ES-10 and FABP were not found in tumor cell lines.…”
Section: -[4-(12-diphenyl-1-butenyl)-phenoxy]-nn-dimethylethanaminementioning
confidence: 99%